Gerakan Islam dan Masa Depan Demokrasi di Era Indonesia Pasca-Soeharto - Asep Nurjaman (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2023)
Since 1998, Indonesia, as the biggest Muslim country in the world, has transformed from an authoritarian to a democratic regime. However, violence and terrorism associated with the Islamic movement, especially the movement of political Islam, are considered to threaten the future of Indonesian democracy. The purpose of the study is to describe the Political Islam Movement and its impact on the post-Suharto democratic system. This study uses qualitative research methods with descriptive analysis research, while the data is obtained through literature review and document analysis. This study found that acts of violence and terrorism were carried out by fundamentalist Muslims who aspired to realize an Islamic state. However, these acts of violence and terrorism triggered the development of moderate Muslims. The consequences of the development of moderate Muslims are the changing of Muslim political behavior, starting from not participating in elections, changing political choices, and up to pragmatic politics. The political violence that has occurred has encouraged the development of Islamic moderation, thus harming Islamic parties because Muslim voters have diverted their political choices to the nationalist-religious parties.